2020
DOI: 10.3389/fnagi.2020.00223
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Biomarkers for Predictive Diagnosis of Cognitive Impairment in a Pakistani Population

Abstract: Numerous studies have identified an association between age-related cognitive impairment (CI) and oxidative damage, accumulation of metals, amyloid levels, tau, and deranged lipid profile. There is a concerted effort to establish the reliability of these blood-based biomarkers for predictive diagnosis of CI and its progression. We assessed the serum levels of high-density lipoprotein (HDL) cholesterol, low-density lipoprotein (LDL) cholesterol, triglycerides, total cholesterol, selected metals (Cu, Al, Zn, Pb,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 92 publications
0
9
1
Order By: Relevance
“…In this study, TAU showed positive correlations with cholesterol ratio (TC/HDL), TG, and LDL and a negative correlation with HDL. Furthermore, Aβ-42 showed positive correlations with TG, LDL, and cholesterol ratio and negative correlations with HDL and TC (22). In our analysis, Apo-A1 also showed a correlation with TAU and P-TAU in the negative Apo-E4 group, while Apo-B did not yield any significant result.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…In this study, TAU showed positive correlations with cholesterol ratio (TC/HDL), TG, and LDL and a negative correlation with HDL. Furthermore, Aβ-42 showed positive correlations with TG, LDL, and cholesterol ratio and negative correlations with HDL and TC (22). In our analysis, Apo-A1 also showed a correlation with TAU and P-TAU in the negative Apo-E4 group, while Apo-B did not yield any significant result.…”
Section: Discussioncontrasting
confidence: 41%
“…Similarly, another systematic review and meta-analysis reported that elevated concentration of LDL could be a potential risk factor for AD and this association is strong in patients in their 60s, which fades with advancing age (21). Other studies emphasized the other lipids and lipoproteins and reported lower serum level of HDL (22) and elevated serum level of TC (23) in the cases with AD. On contrary, some studies reported that late-life hypercholesterolemia might slow cognitive decline, particularly in combination with other cerebrovascular risk factors, possibly due to enhanced cerebral perfusion (24).…”
Section: Discussionmentioning
confidence: 93%
“…They found that increased cholesterol in the plasma was leading to increased beta-amyloid production. Many other studies found the same association between cholesterol and beta-amyloid plaques in the brain [4,24]. Some studied proved that beta-amyloid isoforms 1-40, 1-42 are associated explicitly with plasma cholesterol [7,13].…”
Section: Figure 2: Demonstrating the Process Of Synthesis Metabolismmentioning
confidence: 77%
“…The study by Iqbal et al was a systematic review showing that increased LDL-C, TC, TG were increasing beta-amyloid production. In contrast, decreased HDL-C was associated with AD [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although we have adjusted the MAPT groups in our analysis, further cohort studies with baseline NfL data are needed to generalize our findings to a wider population. Moreover, besides NfL, other cognition-related blood biomarkers, such as brain-derived neurotrophic factor, 3-hydroxykynurenine, lipid levels and total-tau 14 , 15 , might also be tested as potential candidates in similar analysis to distinguish cognitive status between the NC and the MCI groups. Despite that we found associations between NfL and global cognitive functions in the MCI group, investigations using a more comprehensive assessment of cognitive functions 7 , 11 , 16 is needed to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%